Revitalizing the Educational Values of Ki Hadjar Dewantara in the Development of Project and Problem-Based Indonesian Language Learning - Nur’aini, Dhiva Maulida Rizqi; Suwandi, Sarwiji; Rohmadi, Muhammad (Proceedings of International Conference on Science, Education, and Technology, 2025)
Revitalizing of Ki Hajar Dewantara's educational values ​​is an important strategy in strengthening students' character amidst the challenges of 21st century education. This study examines the application of these values ​​in developing project-based and problem-based Indonesian language learning at the junior high school level. This learning model is considered capable of encouraging active student involvement, improving critical thinking skills, and building awareness of national values ​​and culture. The study used a descriptive-qualitative approach within a development research framework. The subjects of the study consisted of junior high school teachers and students in Boyolali Regency. Data were obtained through observation of the learning process, interviews, documentation, and expert validation of the designed learning tools. Data were analyzed thematically to identify the form of integration of Ki Hajar Dewantara's values ​​in learning activities. The results of the study indicate that the principles of Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani can be implemented functionally in project-based and problem-based learning. Value integration is carried out through the selection of contextual themes, collaborative assignments, and reflection of values ​​in each stage of the project. Positive impacts are seen in increasing student involvement, strengthening the value of responsibility, and growing cultural awareness. Teachers also showed an increase in understanding in implementing character education values ​​concretely. In conclusion, the integration of Ki Hajar Dewantara's teachings in the development of project-based and problem-based Indonesian language learning provides a significant contribution to achieving holistic educational goals. This model is relevant to be applied more widely in the context of character-based learning.